Historical milestones in the study of pulmonary hypertension - Anna K. Osokina; Oleg V. Rodnenkov; Tamila V. Martynyuk (Терапевтический архив)
The article describes the historical aspects of the discovery of the pulmonary circulation and the study of pulmonary hypertension (PH) as a pathophysiological condition with a key hemodynamic characteristic – an increase in pressure in the pulmonary artery. The complexity of PH treatment is due to the association with various cardiovascular and respiratory diseases, which requires a multifaceted holistic interdisciplinary approach with the active participation of the physician and the patient. Currently, the guide for successful clinical practice are clinical guidelines covering the full range of diagnostic and therapeutic measures for various groups of PH. The development of guidelines is the result of a long way of studying morphology, pathophysiology, creating and researching of pathogenetic medical drugs, clinical observation of patients in the framework of studies and registries.